A Review of Foreign Language Learners’ Emotions - Yu, Qiangfu (Frontiers in Psychology, 2022)
In the past half century, the research on foreign language learners (FLL) emotions has shifted the focus from an exclusive analysis of negative emotions to a more holistic study of both negative emotions and positive emotions, and currently to mediators of multiple emotions. Of the FLL negative emotions, foreign language anxiety (FLA) attracts the most attention. Researchers have widely discussed the relationship between FLA and foreign language achievement, the influencing factors of FLA as well as regulation and intervention strategies of FLA. Foreign language enjoyment (FLE) is the most heavily studied research subject on FLL positive emotions. Researchers generally focus on the influencing factors of FLE and the relationship between FLE and FLA. With the implementation of holistic education, emotional intelligence (EI), a mediator of multiple emotions of FLL, has been becoming a newly hot topic in the field of FLL emotions. By reviewing the previous studies, this paper proposes that the future research on FLL emotion needs to expand the theoretical perspective, enrich the research topics, and innovate the research methods.